Alexithymia and Depression Affect Quality of Life in Patients With Chronic Pain: A Study on 205 Patients With Fibromyalgia - Tesio, Valentina; Di Tella, Marialaura; Ghiggia, Ada; Romeo, Annunziata; Colonna, Fabrizio; Fusaro, Enrico; Geminiani, Giuliano C.; Castelli, Lorys (Frontiers in Psychology, 2018)
Pain in Fibromyalgia (FM) is accompanied by a heterogeneous series of other symptoms, which strongly affect patients’ quality of life and interfere with social and work performance. The present study aimed to evaluate the effects of alexithymia on both the physical and psychosocial components of the health related quality of life of FM patients, controlling for the concomitant effects of depression, anxiety, and pain. In particular, given the strong interconnection between depression and alexithymia, the relationship between alexithymia and health related quality of life (HRQoL) as mediated by depressive symptoms was further investigated. Data were collected on a consecutive sample of 205 female patients with a main diagnosis of FM. The results showed that about 26% of the patients showed the presence of alexithymia, as assessed by the Toronto Alexithymia Scale (TAS-20). Clinically relevant levels of depressive and anxiety symptoms were present in 61% and 60% of the patients, respectively. The results of the hierarchical multiple regression analyses showed that pain intensity and depressive symptoms explained the 45% of the variance of the physical component of HRQoL (p< .001). Regarding the mental component of HRQoL, depressive and anxiety symptoms, alexithymia and pain intensity significantly explained 61% of the variance (p < .001). The mediation analyses confirmed that alexithymia had a direct effect on the mental component of HRQoL and showed a statistically significant indirect effect on both the physical and mental components, through the mediation of depressive symptoms. In conclusion, the results of the present study suggested the presence of both a direct and an indirect effect of alexithymia, in particular of the difficulty identifying feeling, on the health related quality of life of patients with FM. Indeed, even though the concomitant presence of depressive symptoms is responsible of an indirect effect, alexithymia per se seems to directly contribute to worsen the impact that this chronic pain pathology has on the patients’ quality of life, especially regarding the psychosocial functioning.